Comparison of glycemic and lipid profiles indicators among obese children and adolescents treated at public or private services from the city of Ribeirão Preto (SP) - Nogueira-de-Almeida, Carlos A.; Pires, Lara A. F.; Santos, Rafaela G. dos (Medicina (Ribeirao Preto), 2016)
Design: Observational cross-sectional. Objectives: To compare the lipid and glycemic profiles of obese children and adolescents, followed at a public or a private health service. Methods: A cross-sectional study involving 113 obese patients, aged 7 to 18 years, conducted at two clinics, one public (n = 51) and the other private ( n = 62). Anthropometric data and blood samples were collected and glucose, insulin, HOMA and lipid profile have been compared between groups. Results: regarding averages, it was observed differences only for HDL, with lower values for public service. The prevalence of indicators outside the normal range, has always been above 45%, with the exception of hyperglycemia witch was rare. Only the prevalence of individuals with low HDL was different between groups, being lower at the private service. Conclusions: there was almost no hyperglycemia, but the prevalence of dyslipidemia and insulin resistance were high in both services. HDL was the only indicator that showed differences between the two groups and, considering that it is the most sensitive to the quality of nutrition and physical activity, it may be suggested that at the public health and on the individual management, these aspects should be better managed in lower income populations